Understanding the Impact of Trust, Perceived Risk, and Perceived Technology on the Online Shopping Intentions: Case Study in Kurdistan Region of Iraq - AHMED, SHEWA YASIN; ALI, BAYAD JAMAL; TOP, CEMIL (The journal of contemporary issues in business and government, 2021)
The paper aims to understand the impact of trust, perceived risk, and perceived technology on the customer intention for online shopping. The online shopping habits are new and emerging in Kurdistan Region of Iraq. In this regard, the data collected to from the region to understand the main reasons those drive of slow the customers to purchase online. The results have shown that perceived risk effected customers’ online shopping intentions negatively. Secondly, perceived technology was affecting the intentions positively. Lastly, it was observed that trust was positively related with the online purchase intentions.